2010
DOI: 10.1186/1471-230x-10-129
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus conventional appendectomy - a meta-analysis of randomized controlled trials

Abstract: BackgroundAlthough laparoscopic surgery has been available for a long time and laparoscopic cholecystectomy has been performed universally, it is still not clear whether open appendectomy (OA) or laparoscopic appendectomy (LA) is the most appropriate surgical approach to acute appendicitis. The purpose of this work is to compare the therapeutic effects and safety of laparoscopic and conventional "open" appendectomy by means of a meta-analysis.MethodsA meta-analysis was performed of all randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
221
6
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(254 citation statements)
references
References 61 publications
15
221
6
12
Order By: Relevance
“…It is also gaining popularity because of shorter operative time, less postoperative pain, and lesser incidence of surgical site infection [8][9][10][11][12][13][14]. Its only drawback is slightly higher rate of intra-abdominal abscess [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It is also gaining popularity because of shorter operative time, less postoperative pain, and lesser incidence of surgical site infection [8][9][10][11][12][13][14]. Its only drawback is slightly higher rate of intra-abdominal abscess [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stay and RTNA are important indicators of patient recovery; many studies have shown that the length of hospital stay and RTNA are shorter in patients who underwent LA than in those who underwent OA (17)(18)(19)(20). In a study on LA conducted by Shaikh et al (17), the hospital stay time and RTNA were found to be 1.7 and 12.6 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A worldwide spread of training in laparoscopic techniques lead to a significant reduction in difference of operative time compared to open procedures after 2000, as evidenced by one of the meta-analyses. 12 In our study, the difference between the duration of postoperative ileus for two different approaches was statistically significant. Recovery of the bowel function was faster in the LA group (30.64±14.24) vs 11.61±4, p Value 0.00).…”
Section: Discussionmentioning
confidence: 75%